ответ: х1= -5; х2=5/2
Объяснение:
(3х-15/2)×(х+5)=0
3х-15/2=0
3х=15/2
х=15/2
х+5=0
х=-5
7,5=15/2
x(3x-7,5)+5(3x-7,5)=0
3x²-7,5x+15x-37,5=0
3x²+7,5x-37,5=0 // * 10
30x²+75x-375=0 // : 15
2x²+5x-25=0
Δ=25+200=225
√Δ=15
X1=(-5-15)/4=-20/4=-5
X2=(-5+15)/4=10/4=2,5
ответ: х1= -5; х2=5/2
Объяснение:
(3х-15/2)×(х+5)=0
3х-15/2=0
3х=15/2
х=15/2
х+5=0
х=-5
7,5=15/2
Объяснение:
x(3x-7,5)+5(3x-7,5)=0
3x²-7,5x+15x-37,5=0
3x²+7,5x-37,5=0 // * 10
30x²+75x-375=0 // : 15
2x²+5x-25=0
Δ=25+200=225
√Δ=15
X1=(-5-15)/4=-20/4=-5
X2=(-5+15)/4=10/4=2,5